Stamp duty land tax - Thomas, Michael (Cambridge University Press, 2003)
The law on stamp duty, based on the Stamp Act of 1891, has been thoroughly overhauled with a new law: Stamp Duty Land Tax (SDLT), introduced by Finance Act 2003. This book provides a detailed overview of SDLT in comparison with the old stamp duty provisions, and highlights the major changes introduced. It includes a detailed discussion of the legislation as well as suggested interpretations and planning opportunities. The volume will appeal to those involved in UK land and buildings transactions: property lawyers, solicitors, conveyancers, surveyors, and tax practitioners